Schiff base metal complex as a potential therapeutic drug in medical science: A critical review - Chaudhary, Narendra Kumar; Guragain, Biswash; Chaudhary, Siyanand Kumar; Mishra, Parashuram (BIBECHANA, 2021)
The discovery of new chemotherapeutics with novel bioactivities and functionalities to fight current emerging diseases has become the most significant research in pharmaceutical science. Schiff bases are versatile pharmacophores that can form complexes by chelation with metals of different oxidation states. Over a few decades of intensive research on metal-based drugs, Schiff base metal complexes have been considered as the active field of research in coordination chemistry, owing to their valuable applications in various fields of science. As therapeutic drugs, they have potential applications as antibiotic, antimicrobial, antitumor, antiviral, anti-inflammatory, analgesic, antifungal, and many more. There has been a global threat of drug resistance in medical science in recent years because most of the pathogenic organisms are developing the ability to deactivate drug substances. For this reason, it requires urgent attention from chemical and pharmaceutical scientists to address the severe challenges of multidrug resistance. This review summarizes the current developments in the last few decades' research on the chemotherapeutic activities of Schiff base metal complexes. BIBECHANA 18 (1) (2021) 214-230